Determinants of Consumer Purchase Behavior in Culinary MSMEs in Jakarta: The Roles of Product Quality, Price, and Promotion - Irwan Zulkifli; Agus Aribowo (Sean Institute, 2026)
This study examines the determinants of consumer purchase behavior in culinary micro, small, and medium enterprises (MSMEs) in Jakarta by focusing on the roles of product quality, price, and promotion. Employing a quantitative explanatory design, a cross-sectional survey was administered to consumers who had purchased from culinary MSMEs in Jakarta, and the data were analyzed using multiple linear regression to estimate both partial and simultaneous effects of the explanatory variables. The findings reveal that product quality, price, and promotion each exert a positive and statistically significant influence on consumer purchase behavior, with promotion demonstrating the strongest relative effect. These results indicate that promotional activities are effective in stimulating initial purchase, while sustained purchasing behavior depends on consistent product quality and perceived price fairness. The study offers managerial implications for culinary MSME owners in Jakarta to implement integrated marketing strategies that align quality management, value-based pricing, and promotional design to enhance consumer value perception and support business sustainability in a highly competitive and digitally mediated urban market.